The tetraspanin network modulates MT1-MMP cell surface trafficking - Schröder, Hannes; Hoffmann, S. C.; Hecker, Markus; Korff, Thomas; Ludwig, Thomas (International journal of biochemistry & cell biology, 2013)
The membrane-type 1 matrix metalloproteinase (MT1-MMP) drives fundamental physiological and pathophysiological processes. Among other substrates, MT1-MMP cleaves components of the extracellular matrix and activates other matrix-cleaving proteases such as MMP-2. Trafficking is a highly effective means to modulate MT1-MMP cell surface expression, and hence regulate its function. Here, we describe the complex interaction of MT1-MMP with tetraspanins, their effects on MT1-MMP intracellular trafficking and proteolytic function. Tetraspanins are credited as membrane organizers that form a network within the membrane to regulate the trafficking of associated proteins. In short, we found MT1-MMP to interact with the tetraspanin-associated EWI-2 protein by a yeast two-hybrid screen. Immunoprecipitation analysis confirmed this interaction and further revealed that MT1-MMP also stably interacts with distinct tetraspanins (CD9, CD37, CD53, CD63, CD81, and CD82) and the tetraspanin-like MAL protein. By using different MT1-MMP truncation constructs and mutants, we observed that all tetraspanins and MAL associated with the hemopexin domain of MT1-MMP. Moreover, this interaction was independent of O-glycosylation of MT1-MMP and exclusively occurred in the endoplasmic reticulum. Here, the respective subcellular compartment was identified by fitting the MT1-MMP interaction pattern to a model for post-translational processing of MT1-MMP. In addition, tetraspanins differentially affected the cell surface localization of MT1-MMP, its capacity to activate pro-MMP-2, and the collagen invasion capacity. Interestingly, the degree of tetraspanin-MT1-MMP association did not correlate with its impact on MT1-MMP function. Tetraspanins thus distinctly affect MT1-MMP subcellular localization and function, and may constitute an effective mechanism to control MT1-MMP-dependent proteolysis at the cell surface.